Ecological Issues in English Language Learning: A Study of Senior High School Students' Perceptions in Dompu Regency (International Forum of Researchers and Lecturers, 2025)
This study investigates how high school students in Dompu Regency perceive the integration of environmental issues into English language education. Using a survey method, data were gathered through an online questionnaire distributed to 45 students from various senior high schools in Dompu between June 15 and July 3, 2025. The research focused on three key aspects: students’ motivation to learn English in real-life contexts, their interest in environmental concerns such as pollution and climate change, and their curiosity about how English lessons can help them understand ways to protect the environment. The findings reveal strong student support for incorporating ecological themes into English learning. Approximately 64.5% of participants expressed a desire to learn English in ways connected to real-life situations. Additionally, 82.2% showed significant interest in exploring environmental issues, while 68.8% indicated they wanted to learn how to care for the environment through English-based activities. These results suggest that students do not view English merely as a subject centered on grammar or academic skills, but rather as a medium for engaging with meaningful and globally relevant issues. In response to these findings, the study recommends that English educators incorporate environmentally themed content into their teaching. Pedagogical strategies such as Eco-ELT (Ecological English Language Teaching) and action-based learning are encouraged, as they can foster both language proficiency and environmental literacy. Through these approaches, teachers can create more meaningful, context-rich learning environments that not only improve students’ English skills but also raise their awareness of sustainability and global responsibility. By blending language instruction with ecological awareness, students are empowered to become more thoughtful, informed, and active participants in addressing the environmental challenges of today’s world.